Some reciprocal roles between behavior analysis and institutional economics in post-darwinian science - Glenn, Sigrid S. (1985)
Behavior analysis and institutional economics are viewed as having common origins in the early 20th century effort to benefit from the conceptual revolution spurred by Darwin's synthesis. Institutional economics, initiated by Thorstein Veblen, appears to have failed to develop a progressive scientific technology, while behavior analysis has done so. It is suggested that institutional economics has been held back by lack of a synthesizing scientific mechanism that elucidates the relation between technological and ceremonial processes, the two cultural forces described by Veblen. The theory of institutional economist C. E. Ayres, built on Veblen's distinction, is used to clarify the concepts of technological and ceremonial processes for the reader. An analysis of the behavioral processes that might underlie the cultural processes described by Veblen/Ayres suggests that the experimental analysis of behavior has provided concepts that might function as a synthesizing mechanism for the social sciences and, in particular, institutional economics. The Veblen/Ayres dichotomy, now seen in terms of underlying behavioral processes, is used to examine the field of behavior analysis in terms of its origins, its relation to psychology and its current state. The paper concludes with a few practical suggestions as to how behavior analysts might work to enhance survival.